Digitalize The Materials Of The Applied Art Of Arabic Translation Course/ رقمنة مواد فنّ الترجمة العربية التطبيقية - Mahdi, Rijal; Sanusi, Anwar; Tahawi, Abdelrahman Moawad Ali (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to shed light on the efforts made to digitalize the materials of the applied art of translation course by converting its materials into video clips and a printed textbook. The importance of this study is also because it reveals methods of teaching translation, as it combines science, art, practice, and application, in addition to the process of digitizing the material. This study followed the descriptive approach that focuses on describing the studied material, dealing with the general description, characteristics, teaching methods, and everything related to it in a complete scientific study. The researchers reached essential results, the most important of which is that the digitization of the materials is possible, and two things did it: digitizing the materials through video clips and issuing the printed textbook. As for the first, it consists of video clips according to the subjects prescribed in the study plan, and in total, there were 14 videos, which helped the learners to understand the materials well, in addition to their possibilities to refer to them when, how, and where they want. The second digitization was done by preparing a printed textbook distinguished by its theoretical and practical aspects, with a lexical witness for all the words used in the models presented, with reference to the extensive dictionary of the Indonesian language.